Efek Parakrin Sel Punca Mesenkimal pada Kultur In-Vitro - Sibuea, Christine Verawaty; Sitanggang, Ervina Julien; Simaremare, Ade Pryta (Universitas HKBP Nommensen, 2024)
Background: MSC, IL-10, TNF-a, IFN-g, PGE2. Background: The high proliferation and differentiation capabilities, paracrine effects and immunomodulatory functions of Mesencymal Stem Cells (MSCs) have been utilized in cellular therapy approaches for infectious and degenerative diseases in the last decade. Paracrine effects MSCs contain growth factors and cytokines, including IL-10, TNF-a, IFN-g and PGE2. There are still debates regarding the role and performance of the levels of paracrine effects of MSCs IL-10, TNF-a, IFN-g and PGE2, so it is necessary to have a model of the performance of these paracrine effects. Objective: To determine the levels of IL-10, TNF-a, IFN-g and PGE2 in basal in-vitro culture conditions, which can be used as a model for MSC immunomodulatory performance. Methods: This research is an in-vitro culture study of MSCs in basal conditions. MSCs were cultured for 21 days and levels of IL-10, TNF-a, IFN-g and PGE2 were examined on the 7th, 14th and 21st days in the culture medium, using the ELISA method. Results: IL-20 was not found in the culture medium until the 21st day, meanwhile TNF-a levels continued to increase until the 21st day. IFN-g was only found on day 7 of culture. PGE2 levels were found to be the highest secreted among the cytokines analyzed, but were not found on day 21. Conclusion: Paracrine effects secreted by MSCs in basal culture conditions due as a response to cell damage that occurs during the duration of culture. The paracrine effects of MSCs can influence each other, so that there can be suppression or induction of secretion of paracrine effects. Keywords: MSC, IL-10, TNF-a, IFN-g, PGE2. Abstrak Latar belakang: Kemampuan proliferasi dan diferensiasi yang tinggi, efek parakrin serta fungsi imunomudulator Mesencymal Stem Cells (MSCs) dimanfaatkan dalam pendekatan terapi seluler penyakit infeksi dan degeneratif dalam dekade terakhir. Efek parakrin MSCs mengandung growth factor dan sitokin, diantaranya IL-10, TNF-a, IFN-g dan PGE2. Banyak perbedaan pendapat tentang peran dan gambaran kadar efek parakrin MSCs IL-10, TNF-a, IFN-g dan PGE2 sehingga diperlukan adanya model gambaran efek parakrin tersebut. Tujuan: Mengetahui kadar IL-10, TNF-a, PGE2 dan IFN-g pada kondisi basal kultur in-vitro, yang dapat digunakan sebagai model gambaran imunomodulator MSC. Metode: Penelitian ini merupakan penelitian kultur in-vitro MSCs pada kondisi basal. MSCs dikultur selama 21 hari dan dilakukan pemeriksaan kadar IL-10, TNF-a, PGE2 dan IFN-g pada hari ke-7, ke-14 dan ke-21 pada medium kultur, dengan menggunakan metode ELISA. Hasil: IL-20 tidak ditemukan pada medium kultur hingga hari ke-21, sedangkan kadar TNF-a semakin meningkat hingga hari ke-21. IFN-g hanya ditemukan pada kultur hari ke-7. Kadar PGE2 ditemukan paling tinggi disekresikan diantara sitokin yang dianalisa, tetapi tidak ditemukan pada hari ke-21. Kesimpulan: Efek parakrin disekresikan MSC pada kultur kondis basal sebagai respon kerusakan sel yang terjadi selama durasi kultur. Efek parakrin MSC dapat saling mempengaruhi, sehingga dapat terjadi supresi atau induksi sekresi efek parakrin. Kata Kunci: MSC, IL-10, TNF-a, IFN-g, PGE2.